2021
DOI: 10.1136/bmjopen-2020-046835
|View full text |Cite
|
Sign up to set email alerts
|

Open-label, randomised, clinical trial to evaluate the immunogenicity and safety of a prophylactic vaccination of healthcare providers by administration of a heterologous vaccine regimen against Ebola in the Democratic Republic of the Congo: the study protocol

Abstract: IntroductionThis article describes the protocol of an Ebola vaccine clinical trial which investigates the safety and immunogenicity of a two-dose prophylactic Ebola vaccine regimen comprised of two Ebola vaccines (Ad26.ZEBOV and MVA-BN-Filo) administered 56 days apart, followed by a booster vaccination with Ad26.ZEBOV offered at either 1 year or 2 years (randomisation 1:1) after the first dose. This clinical trial is part of the EBOVAC3 project (an Innovative Medicines Initiative 2 Joint Undertaking), and is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Outside outbreak situations, whether a booster dose is needed after an interval of time from the first vaccination, and the optimal timing for booster administration, still remain to be established. Results from the ongoing VAC52150EBL2007 study will elucidate if there is any difference in the elicited immune response if the booster dose is given either 1 year or 2 years after the first vaccination, 19 while another booster study, VAC52150EBL2010 (NCT05064956), assessing the safety and immunogenicity of a booster dose in previously vaccinated HIVpositive adults, will also provide long-term immunogenicity data after more than 4 years from initial vaccination with the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen in this group. Further research is also needed to define the best approach for the administration of the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen in paediatric populations in countries with Ebola risk; for example, whether vaccination should be given through campaigns or integrated within the routine paediatric immunisation schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Outside outbreak situations, whether a booster dose is needed after an interval of time from the first vaccination, and the optimal timing for booster administration, still remain to be established. Results from the ongoing VAC52150EBL2007 study will elucidate if there is any difference in the elicited immune response if the booster dose is given either 1 year or 2 years after the first vaccination, 19 while another booster study, VAC52150EBL2010 (NCT05064956), assessing the safety and immunogenicity of a booster dose in previously vaccinated HIVpositive adults, will also provide long-term immunogenicity data after more than 4 years from initial vaccination with the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen in this group. Further research is also needed to define the best approach for the administration of the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen in paediatric populations in countries with Ebola risk; for example, whether vaccination should be given through campaigns or integrated within the routine paediatric immunisation schedule.…”
Section: Discussionmentioning
confidence: 99%
“…GamEvac-Combi is a VSV-Ad5 prime-boost EBOV vaccine [ 41 ]. The monovalent Ad26-ZEBOV vaccine provides acquired immunity to the Zaire EBOV, which is active and specific [ 57 ]. The recent vaccines that are in clinical trials are Ad26.ZEBOV, MVABN-Filo, rVSV#GZEBOV-GP from Zaire EBOV, which was developed in the countries of Guinea, Liberia, Mali, and Sierra Leone and is in phase 2 of the clinical trial, with the status of active and not recruiting (2017–2024) [ 58 ], GamEvac-Lyo, GamEvac-Lyo (component A), GamEvac-Lyo (component B) from Zaire EBOV, which is in the country of the Russian Federation and has completed phase 1 and phase 2 of the clinical trial (2017–2018) [ 41 ], VSV-GZEBOV, ChAd3-EBO Z from Zaire EBOV, which was developed in the country of Liberia and is in phase 2 of the clinical trial (2015–2020) [ 59 ], HPIV3/#HNF/EbovZ GP vaccine from Zaire EBOV, which was developed in the country of the USA and is in phase 1 of the clinical trial (2018–2020) and is in active and not recruiting stage, ChAd3-EBO-Z, MVA Multi-Filo Ebola vaccine from Mayinga EBOV, which was developed in the USA and has completed phase 1 of the clinical trial (2018–2020) [ 16 ], cAd3-EBO S vaccine from Zaire EBOV (Mayinga), which was developed in Uganda and has completed phase 1 of the clinical trial (2019–2020) [ 34 ], and cAd3-Marburg cAd3-EBO-S from Zaire EBOV (Mayinga), which was developed in the USA and is in recruiting phase 1 of the clinical trial (2021) [ 34 ].…”
Section: Current Vaccine Considerationsmentioning
confidence: 99%
“…In an attempt to prepare this area for future outbreaks, this vaccine trial specifically targeted health care providers (HCP) and frontliners as participants, as they are not only more at risk of contracting infectious diseases but may also contribute to the spread of these diseases [17][18][19][20]. In total 700 participants were planned to be recruited and vaccinated with a two-dose heterologous vaccine regimen (Ad26.ZEBOV (Zabdeno Ò ) as the first dose and MVA-BN-Filo (Mvabea Ò ) as the second dose, at a 56-day interval) followed by a booster Ad26.ZEBOV (Zabdeno Ò ) dose, administered either one or two years (randomization 1:1) after the initial dose [21]. This trial was established through an international partnership between the University of Antwerp (UAntwerp) as sponsor and the University of Kinshasa (UNIKIN) as principal investigator (PI).…”
Section: Introductionmentioning
confidence: 99%
“…This trial was established through an international partnership between the University of Antwerp (UAntwerp) as sponsor and the University of Kinshasa (UNIKIN) as principal investigator (PI). Further details of the trial design can be found in Larivière et al 2021 [21].…”
Section: Introductionmentioning
confidence: 99%